Effects of protein S-nitrosylation on the glycogen metabolism in postmortem pork. (30th January 2019) - Zhang, Lili; Liu, Rui; Cheng, Yuping; Xing, Lujuan; Zhou, Guanghong; Zhang, Wangang
Highlights: High level of NO concentration inhibited the rate of energy metabolism. Infusion of NOS inhibitor leaded to fast rate of glycolysis in pork. Activity of key glycolytic enzymes was regulated by protein S-nitrosylation. Abstract: The aim of this study was to investigate the effects of protein S-nitrosylation on the glycogen metabolism in postmortem pork. The pork samples were incubated with control (0.9% NaCl), nitric oxide synthase (NOS) inhibitor, or NO donor for 4 and 12 h at 4 °C. Results indicate that NOS inhibitor treatment led to significantly lower level of glycogen and higher lactate content at 24 h compared those of control and NO donor treatments ( P < 0.05). The pH of NOS inhibitor treatment was significantly lower than other treatments, which indicates the fast glycolysis during postmortem aging ( P < 0.05). In addition, the activities of glycolytic enzymes including GP, GAPDH and PK were significantly different among three treatments ( P < 0.05) possibly due to the different modification of protein S-nitrosylation. These results suggest that NO could regulate the glycogen metabolism through modulating the activities of glycolytic enzymes by protein S-nitrosylation.